Кристалізація складних фосфатів у розплавах системи K2O–P2O5–TiO2–ZnO - Огородник, І.В.; Затовський, І.В.; Слободяник, М.С. (Видавничий дім "Академперіодика" НАН України, 2007)
The crystallization fields and conditions of the formation of complex phosphates have been studied for the flux system K2O–P2O5–TiO2–ZnO. KTi2(PO4)3, KTiOPO4, K2Zn0.5Ti1.5(PO4)3, K1+yZnxTi2–x(PO4)3 (0 ≤ x ≤ 0.5; 0 ≤ y ≤ 1) and KZnPO4 are synthesized. The cell parameters of the obtained compounds are calculated by the powder XRD. Ti4+ → Ti3+ reduction processes are observed during the crystallization of langbeinite-like phosphates. The presence of titanium(III) in the obtained compounds is discovered using EPR- and electron spectroscopy.